Analisis pandangan politik Harun Taib: Kajian terhadap karyanya berbilang-bilang Jamaah / Mohd Khairul Amin Haji Zakaria - Mohd Khairul Amin , Haji Zakaria (2018)
This study is to highlight the political views of Harun Taib in the issue of variety of aljamā„ ah. This study is also to understand in more details the way of thinking from the perspective of an Islamic political leader who is directly involves in the political field in resolving a problem. The objective of this study is to identify, examine and analyze whether the socio-life of Harun Taib has profound impact to his political views upon the issue of variety of al-jamā„ah. Besides, this study will touch upon his writing‟s methodological approach and political views in his books of “Berbilang-Bilang Jamaah”. The analysis of descriptive qualitative will be the main methodological approach in this research through data collection and analysis mainly from the instrument of library study, field study and documents analysis. Comprehensively, this study will be using his book, “Berbilang-Bilang Jamaah” as the main reference of the study as well as looking at other literature reviews written by various parties as the supportive sources of the study. In addition, in order to further strengthen the findings of the study, there are selected interviews comprising the nearest family and the parties who directly involves in the same circle of politics for more detailed information. The findings show that the individual socio-life of Harun Taib, high level of knowledges and his experiences in politics will be the influential factors to his political views of the issue of variety of al-jamā„ah. High quality of analysis and reliability of resources in his book of “Berbilang-Bilang Jamaah” has contributed to a moderate political views based on maqāṣid al-Sharī„ah and it is very important for the unity of ummah in present and future.